Effect of broiler genetics, age, and gender on performance and blood chemistry. Issue 7 (July 2020) - Livingston, M.L.; Cowieson, A.J.; Crespo, R.; Hoang, V.; Nogal, B.; Browning, M.; Livingston, K.A.
Abstract: A total of 640 broilers were used to determine the effects of strain, sex, and age on hematology and blood chemistry using rapid detection devices. Day old chicks from two genetic lines of common fast-growing and high-yield broiler strains were sexed and allocated to 40 pens (16 birds per pen) containing either male or female and Ross or Cobb strains (n = 10). Venous blood was analyzed weekly using 2 broilers from each pen (n = 20) using the i-STAT® Alinity Handheld Clinical Analyzer, Zoetis Vetscan VS2, and iCheck™ Carotene devices at 14, 21, 28, 35, and 42 d, as well as growth performance. Post-mortem health tracking metrics were also recorded on 42 d. Broilers were deemed healthy based on posting data results and performed in accordance with industry standards with males presenting greater BW and reduced FCR than female broilers. Ross broilers displayed greater BW to 14 d with similar FCR compared with Cobb birds. Day of age had a highly significant impact on blood calcium, phosphorus, potassium, sodium, chloride, carotene, aspartate aminotransferase, creatine kinase, bile acids, uric acid, total protein, albumin, globulin, total carbon dioxide, hematocrit, and malondialdehyde. Male broilers had reduced blood sodium, chloride, carotene, uric acid, albumin, and increased total protein, glucose, and total carbon dioxide. Ross broilers had greater blood potassium, and sodium, as well as reduced uric acid, total protein, globulin, and malondialdehyde, compared with Cobb birds. These results demonstrated the effectiveness of point-of-care devices in measuring blood chemistry and hematology in modern broilers. These data can be utilized to determine normal healthy blood ranges in these types of broilers when accounting for strain, sex, and age. Abstract : Broiler, Biomarkers, Blood physiology, Rapid point-of-care detection, Animal breeding, Animal product, Biochemistry, Animal physiology, Veterinary science.